2011
DOI: 10.1002/ceat.201100054
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Pressure Swirl Atomizers

Abstract: The prediction of droplet size distributions for atomization nozzles is important for process design and improvement of industrial spraying processes. However, especially for non-Newtonian liquids, the published research applicable for engineering purposes is rare. To derive fundamental correlations for droplet size distributions in the future, the multiphase flow inside the spray nozzle is investigated by computational fluid dynamics, and measurements of droplet size distributions are done under the same flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…The effect of airflow on spatial velocity distribution in the absence of airflow (case a), when Q a = 1000 m 3 h -1 (case b), and when Q w = 0.52 m film. This result is in accordance with the finding of Renze and Zhang [16,29].…”
Section: Velocity and Vorticity Field Distributionsupporting
confidence: 93%
See 2 more Smart Citations
“…The effect of airflow on spatial velocity distribution in the absence of airflow (case a), when Q a = 1000 m 3 h -1 (case b), and when Q w = 0.52 m film. This result is in accordance with the finding of Renze and Zhang [16,29].…”
Section: Velocity and Vorticity Field Distributionsupporting
confidence: 93%
“…Renze and Soni [13,16] confirmed that the main reason for liquid film breakage is under the effect of surface tension and viscosity force. Moreover, external action will change the shape of swirl atomization and affect the degree of droplet refinement and fragmentation.…”
Section: Droplet Average Particle Size D 32mentioning
confidence: 93%
See 1 more Smart Citation
“…Binnie and Harris (1950) studied the effect of surface tension for the dynamics of the air core theoretically and concluded that it is negligible. Numerical studies on pressure-swirl atomizer inner nozzle flow are numerous but relevant for this study are the works of Dash et al (2001), Fu (2016), Galbiati et al (2016b) and Renze et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of droplet size distributions for atomization nozzles is important for the process design and the improvement of industrial spraying processes [1]. In one of the recent researches, the spray flow structure, droplet Sauter mean diameter, and droplet impingement energy were characterized at predefined axial distances and pressure drops.…”
Section: Introductionmentioning
confidence: 99%